1996
DOI: 10.1016/0304-3959(95)00082-8
|View full text |Cite
|
Sign up to set email alerts
|

A comparison of morphine, pethidine and fentanyl in the postsurgical patient-controlled analgesia environment

Abstract: This study was designed to evaluate whether there is any scientific basis for clinicians' preferences for selecting opioids for use in patient-controlled analgesia (PCA) and to determine whether there are any patients' preferences for being treated with any of these opioids. Results were obtained for 55 postoperative patients recruited to investigate putatively equivalent doses of 3 commonly used opioids--morphine, pethidine and fentanyl--when self-administered postoperatively. No significant differences in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
43
0
3

Year Published

1997
1997
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 94 publications
(47 citation statements)
references
References 11 publications
1
43
0
3
Order By: Relevance
“…Lerman [2] and Watcha & White [3] suggest that the incidence of postoperative nausea and vomiting has remained fairly constant for decades with Ϸ20-30% of patients suffering from these unpleasant side-effects. However, it is common to find reports of a much higher incidence in a variety of surgical populations [4][5][6][7][8][9][10]. Differentiation of opioidinduced nausea and vomiting from that of other perioperative factors, including those associated with uncontrolled pain [11], is difficult enough without complications introduced by patient-controlled analgesia (PCA) which allows patients to medicate on irregular and inconsistent bases.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Lerman [2] and Watcha & White [3] suggest that the incidence of postoperative nausea and vomiting has remained fairly constant for decades with Ϸ20-30% of patients suffering from these unpleasant side-effects. However, it is common to find reports of a much higher incidence in a variety of surgical populations [4][5][6][7][8][9][10]. Differentiation of opioidinduced nausea and vomiting from that of other perioperative factors, including those associated with uncontrolled pain [11], is difficult enough without complications introduced by patient-controlled analgesia (PCA) which allows patients to medicate on irregular and inconsistent bases.…”
Section: Discussionmentioning
confidence: 99%
“…His findings suggested that there were few differences in the incidence of nausea and emesis reported between most agents, with the exceptions of nalbuphine, nefopam and pethidine [29]. While Lehmann [29] found only 8% of patients experienced nausea and only 5% reported emesis while receiving pethidine, others have found a much higher incidence of postoperative nausea and vomiting associated with this opioid [30,10]. A study conducted at the authors' institution found no notable differences in the incidence of nausea and vomiting of patients receiving morphine, pethidine or fentanyl for postoperative pain, with Ϸ 60% of patients experiencing nausea and 40% reporting vomiting.…”
Section: Decreasing the Incidence Of Postoperative Nausea And Vomitingmentioning
confidence: 99%
“…In another study by Woodhouse et al, [14] the mean VAS was similar in both groups, but total drug consumed by fentanyl group was significantly more (143 ± 86 mg) than morphine group (82 ± 50 mg). In our study, it also has shown similar results by 72 h.…”
Section: Discussionmentioning
confidence: 71%
“…In a study by Claxton et al, [14,15] they found that nausea was more in morphine group than in fentanyl group. In another study by Niiyama et al, [9] they observed that there was no significant difference in the incident of nausea between the groups.…”
Section: Discussionmentioning
confidence: 96%
“…The effective dose range of some full agonists is limited by side effects (e.g., pethidine and its metabolite, norpethidine, is a convulsant). Most studies on the use of different opioids administered by patient-controlled alagesia (PCA) suggest that there is little to choose between opioids [2,3].…”
mentioning
confidence: 99%